Role of Septins in Endothelial Cells and Platelets - Neubauer, Katharina; Zieger, Barbara (Frontiers in Cell and Developmental Biology, 2021)
Septins are conserved cytoskeletal GTP-binding proteins identified in almost all eukaryotes except higher plants. Mammalian septins comprise 13 family members with either ubiquitous or organ- and tissue-specific expression patterns. They form filamentous oligomers and complexes with other proteins to serve as diffusions barrier and/or multi-molecular scaffolds to function in a physiologically regulated manner. Diverse septins are highly expressed in endothelial cells and platelets, which play an important role in hemostasis, a process to prevent blood loss after vascular injury. Endothelial septins are involved in cellular processes such as exocytosis and in processes concerning organismal level, like angiogenesis. Septins are additionally found in endothelial cell-cell junctions where their presence is required to maintain the integrity of the barrier function of vascular endothelial monolayers. In platelets, septins are important for activation, degranulation, adhesion, and aggregation. They have been identified as mediators of distinct platelet functions and being essential in primary and secondary hemostatic processes. Septin-knockout mouse studies show the relevance of septins in several aspects of hemostasis. This is in line with reports that dysregulation of septins is clinically relevant in human bleeding disorders. The precise function of septins in the biology of endothelial cells and platelets remains poorly understood. The following mini-review highlights the current knowledge about the role of septin cytoskeleton in regulating critical functions in these two cell types.